2019
DOI: 10.1049/iet-epa.2018.5752
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics analysis of printed circuit board winding for high‐speed axial flux permanent magnet motor

Abstract: Gearless and compact motors rotating at speeds above 10,000 rpm are finding many applications nowadays. This study presents the multiphysics modelling and analysis of a multilayer printed circuit board (PCB) stator for high-speed, lowpower axial flux permanent magnet motor. The possibility of circulating current in the multilayer PCB is studied. The two major effects of eddy currents at high frequencies: skin effect and proximity effect are investigated for the PCB winding. The losses in the PCB stator are est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The second as shown in Fig. 3 b has interior permanent magnets (IPMs), in which the PMs are embedded inside the rotor [1, 13, 20, 44]. Since the PMs are buried in the rotor iron, they are protected from corrosion and high centrifugal forces, which can make them a suitable option for high‐speed applications [45].…”
Section: Initial Design Choices and Considerations In Pcb Motorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second as shown in Fig. 3 b has interior permanent magnets (IPMs), in which the PMs are embedded inside the rotor [1, 13, 20, 44]. Since the PMs are buried in the rotor iron, they are protected from corrosion and high centrifugal forces, which can make them a suitable option for high‐speed applications [45].…”
Section: Initial Design Choices and Considerations In Pcb Motorsmentioning
confidence: 99%
“…In [87] a linear motor has been developed for factory automation, consisting of a novel FPCB winding, it is shown that the proposed PCB winding is an appropriate solution for the slotless linear motor. An AFPM PCB motor for high speed, low‐power applications was described in [13, 22, 44], since the Halbach array configuration is used, the flux production and the motor performance is enhanced.…”
Section: Pcb Motors Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, a novel YASA in-wheel motor with tapewound AMM segments for a solar-powered electric vehicle is proposed. During the design process, a multiphysics analysis including electromagnetic, thermal, and mechanical behavior is indispensable [35]- [38]. This paper describes the design, the study and the construction of the prototype of the YASA in-wheel motor with 24 poles and 27slots.…”
Section: Introductionmentioning
confidence: 99%
“…Research on all motors including AFPM motors can be largely categorized into analysis and design, materials, and control. Analysis and design research mainly focuses on multiphysics modeling, such as electromagnetic field, stress, vibration, noise, and heat, design through these analyses, and analytical methods to reduce the analysis time and cost of the motors [9]- [11]. Materials research is actively conducted for the purpose of improving performance or reducing manufacturing costs by using materials such as amorphous cores and ferrite magnets [12]- [14].…”
Section: Introductionmentioning
confidence: 99%